“Family. Oh! The Family!” – Portrayals of Family as an Educational Environment in Selected Literary Works from the 19th And 20th Centuries - Gandecka, Kamila (Pedagogika, 2013)
The family, as the basic microstructure of social life, constitutes, at the very least by supposition, the first and foremost educational environment of a child; an environment which should correspond to the child’s natural needs, especially psychological ones, such as the need for love, unconditional acceptance, the need for respect and recognition, activity, independence, and self-realization [9]. This why M. Lukšienė states, “A good family home is the basis of human physical and spiritual life; it guarantees one’s efficient, creative activity”. The parents’ worldview plays an important role in education, providing an answer to the fundamental questions concerning our existence: Who am I? What sense does my life have? What is the goal of my life? What ideals and rules of action do I represent? What is the world and my place within it? Undoubtedly, a variety of factors affect the shaping of a young person’s worldview, among them school, religion, ideology, the level of social development, social organization, the particular historical period in which the person lives, as well as certain individual psychological predispositions. Nevertheless, parents have always played the pivotal role in the shaping of children’s worldview. Parents prepare their children for an independent life in society by teaching them values, norms, models of behavior, and cultural customs. In this way, parents fulfil their function as a microstructure, fulfilling aims that support the macrostructure. Beginning with the second half of the 19th century, the notion of the family becomes one of the main themes in Polish literature, appearing in the works of such authors as Bolesław Prus, Henryk Sienkiewicz, Eliza Orzeszkowa, Stefan Żeromski, Władysław Reymont, and Maria Konopnicka. Moreover, the literary representation of the family as an educational environment of a child is also often evoked in the theoretical musings of professionals in the field of education. Thse professionals include Helena Radlińska, Jerzy Ostrowski, Janusz Korczak, and Aleksandra Kamiński. In conclusion, the broadly defined notion of family is, without question, universal and timeless. As an area of scholarly inquiry, it requires an interdisciplinary approach that encompasses all possible perspectives.